1998
DOI: 10.1002/masy.19981290111
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Study of the grafting of 13C labeled maleic anhydride onto PE, PP and EPM

Abstract: The chemical structure of polyolefins grafted with maleic anhydride (MA) has been the subject of much speculation, but thorough experimental studies are rare. MA with 99% 13C in the double bond was synthesized and grafted onto PE, EPM and PP in the melt and solution. 1D INADEQUATE 13C NMR spectroscopy was used to characterize the products. Saturated, monomeric MA graft structures are formed. Only for grafted PE short MA oligomers are demonstrated. Grafting occurs on secondary and tertiary carbons depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…On the other hand, in the grafting reactions with MA, grafting mainly occurred on secondary carbons when long methylene sequences were present (>3). Otherwise, grafting also occurred ontertiary carbons 24. The studies of free‐radical grafting reactions on model compounds onto polyolefins showed the presence of 8–40 species, depending on the reaction conditions and how enormously complicated the radical grafting reactions in polyolefins could be 25…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the grafting reactions with MA, grafting mainly occurred on secondary carbons when long methylene sequences were present (>3). Otherwise, grafting also occurred ontertiary carbons 24. The studies of free‐radical grafting reactions on model compounds onto polyolefins showed the presence of 8–40 species, depending on the reaction conditions and how enormously complicated the radical grafting reactions in polyolefins could be 25…”
Section: Resultsmentioning
confidence: 99%
“…This is especially true for 13 C‐NMR, due to the superior sensitivity of the carbon nuclei to the chemical environment. Although various examples can be found in the literature,17–20 there is a number of issues inherent to the nature of PP‐ g ‐MA that usually limits the interpretation of the NMR spectra. First, the usually low grafting yield of MA onto PP, and the limited solubility of high molecular weight PP‐ g ‐MAs often lead to signal‐to‐noise ratios not suitable for accurate quantitative analysis of the grafted moieties.…”
Section: Introductionmentioning
confidence: 99%
“…First, the usually low grafting yield of MA onto PP, and the limited solubility of high molecular weight PP‐ g ‐MAs often lead to signal‐to‐noise ratios not suitable for accurate quantitative analysis of the grafted moieties. On the other hand, various types of grafted anhydride species have been suggested in the literature (succinic,17–19, 12, 21–23 maleic,23 and itaconic anhydrides,18, 19, 23 as well as oligomers,12, 21 etc); if at least two different types of grafted species are present, each one will have a particular chemical environment and therefore a specific set of chemical shifts, making both detection and interpretation more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Different doublets originating from the enriched carbons were displayed, the υ values of which gave an insight into the kind of grafting. 97 Configuration. Polymerization of the diolefin 16 by radicals yields a polymer the 2D-INADEQUATE spectrum of which (Fig.…”
Section: H T H T H T H T H T (A) H T H T T H H T H T (B) Inverted Unitmentioning
confidence: 98%